Dynamics of immigrant resentment in Europe - Katja Salomon (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2020)
A test of social explanations of immigrant resentment - contact, threatened responses, grievances, social disintegration, political persuasion, socialization contexts - across 30 European countries between the years 2002-2016 (N=308.430) provides the background for a comprehensive discussion of how these mechanisms interact and connect to migration patterns. Most susceptible to resentment are those (1) lacking opportunities or (2) easy to persuade. (1) Socioeconomic status, place of residency, grievances, social disintegration, immigrant presence, birth cohort interact to provide/inhibit opportunities for social, economic participation (for natives and migrants) leading to less/greater resentment. (2) Threatened responses are concerns over potential consequences of certain kinds of immigration and are linked to individual characteristics that increase exposure and susceptibility to party cueing, policy signaling and media bias. At the contextual-level, these processes are self-mitigating: Affluent, high-immigration countries more easily sustain tolerance for the same reasons they attract immigrants (opportunities) but are more prone to threatened responses since these are provoked by immigration characteristics overrepresented in affluent countries. While this dynamic is reversed in less advantaged countries, it is also vulnerable to disruption explaining higher resentment in certain countries. Self-mitigating shapes resentment in urban areas as well, but urbanization disrupts regional dynamics, leaving rural Europe especially susceptible to resentment.
Keywords: 300; immigration attitudes; contact; threat; deprivation; disorder; party cues; geopolitical threat